2008
DOI: 10.1111/j.1440-1746.2008.05341.x
|View full text |Cite
|
Sign up to set email alerts
|

Management and patient survival in hepatocellular carcinoma: Does the physician's level of experience matter?

Abstract: The survival of HCC patients was dependent on the level of experience of the physicians who oversaw these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…3,24 We were able to confirm that baseline peripheral blood NLR, a biomarker comparing tumor inflammation and host immunity, was associated with increased mortality in early stage HCC patients undoing RFA. Therefore, we eliminated important confounders on cancer mortality such as difference in tumor stage, treatment decision and level of physician experience.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…3,24 We were able to confirm that baseline peripheral blood NLR, a biomarker comparing tumor inflammation and host immunity, was associated with increased mortality in early stage HCC patients undoing RFA. Therefore, we eliminated important confounders on cancer mortality such as difference in tumor stage, treatment decision and level of physician experience.…”
Section: Discussionmentioning
confidence: 69%
“…3,24 Artificial ascites creation by intra-peritoneal glucose water injection for lesions abutting visceral organ and abdominal wall were routinely performed after July 2008. 3,24 Artificial ascites creation by intra-peritoneal glucose water injection for lesions abutting visceral organ and abdominal wall were routinely performed after July 2008.…”
Section: Index Rfa For Initial Tumorsmentioning
confidence: 99%
“…A case-control study of NAFLD patients highlighted a potentially protective role for the Val227Ala variant of PPAR α against obesity compared to subjects with the wild-type receptor (Chen et al, 2008a). The adipocyte differentiation regulator, PPARγ, plays an important role in lipid homeostasis and insulin sensitivity by enhancing fatty acid and insulin-dependent glucose uptake in adipose tissue (Kallwitz et al, 2008).…”
Section: Nafld and Drug Dispositionmentioning
confidence: 99%
“…Another study showed that the experience of primary care physicians in managing patients with acquired immunodeficiency syndrome has been significantly associated with the survival of their patients [3]. Similarly, another study reported that the survival of patients with hepatocellular carcinoma depends on the level of experience of the physicians overseeing them [4]. An association of physician experience with tuberculosis and survival in patients with active tuberculosis has also been reported [5].…”
Section: Discussionmentioning
confidence: 94%